CONSUMO DE BEBIDA ALCOÓLICA NA GRAVIDEZ: fatores associados e prejuízos na relação mãe-filho. - ARAÚJO, Adely Fátima Dutra Vieira (2017)
The research related to the alcoholic consumption in pregnancy (ACP) presents controversies regarding the factors associated with it. Regarding the effect of this consumption on the mother-child relationship, there are no studies that address such causality. The objective of this study was to investigate the prevalence and factors associated with ACP in 5212 women interviewed immediately after childbirth, and to investigate the causal effect of this consumption on losses in the mother-child relationship (LMCR) in 3210 mothers who answered a questionnaire about their mental health between the 13-35 months of their children's lives, both samples are from São Luís, Maranhão, belonging to the BRISA birth cohort. In the first article, to evaluate associations, we used hierarchical analysis, with Poisson regression with robust variance adjustment. The ACP prevailed in 14.5% of the women interviewed. Higher proportions of this consumption occurred in women with low schooling (0-4 years of study PR 1.59, 5-8 years of study PR 2.28 and of 9-11 years of study PR 1.48), who did not declare themselves white (PR 1.31), without partner (PR 1.49), did not plan for pregnancy (PR 1.27), smoked during the current pregnancy (PR 3.38) and had a history of abortion (PR 1.44). In the second article the Postpartum Bonding Questionnaire was used to evaluate LMCR. The theoretical model of this causal relationship was drawn in the Directed Acyclic Graph (DAG), which proposed for minimum adjustment: maternal age, schooling, family income, occupation, marital status, pregnancy planning and prenatal care. To estimate the causal effect between ACP and LMCR, considering the predictor variables of the minimum adjustment set, that made up the model, we used causal inference, by means of the technique of weighting by the inverse of probability selection. ACP presented a causal effect on LMCR, non-abusive consumption showed coef. 0.049; 95% CI 0.001-0.098; p = 0.04 and abusive consumption had coef. 0.061; CI 95% 0.006; 0.130 and p = 0.07. The equilibrium between the groups exposed and not exposed to ACP was reached, because the balance was effective. It is concluded that more attention is needed from health professionals on the issue of alcohol use during prenatal care, with a view to preventing possible damages in the relationship between mothers and their children.